To find the value of \( A \) that makes the equation true, you need to compute the expression on the right side:
\[ A = 5 - \frac{11}{3} \]
First, convert \( 5 \) to a fraction with a denominator of \( 3 \):
\[ 5 = \frac{15}{3} \]
Now substitute that back into the equation:
\[ A = \frac{15}{3} - \frac{11}{3} \]
Now, subtract the fractions:
\[ A = \frac{15 - 11}{3} = \frac{4}{3} \]
So, the expression for \( A \) is:
\[ A = \frac{4}{3} \]
This means that for the equation \( A = 5 - \frac{11}{3} \) to be true, \( A \) must equal \( \frac{4}{3} \).